2015
DOI: 10.3382/ps/pev215
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two LED Light Bulbs to a Dimmable CFL and their Effects on Broiler Chicken Growth, Stress, and Fear

Abstract: The poultry industry is currently undergoing a shift to alternative lighting sources as incandescent lights become less available. While LED and CFL bulbs both have associated increased energy savings, they may affect the bird's growth and well-being differently as they output different light spectrums. To determine how different LED bulbs and a CFL bulb affected broiler performance, behavior, stress, and overall well-being, we conducted an experiment using Cobb broiler chickens (N=360). A NextGen LED bulb (Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 37 publications
2
46
0
3
Order By: Relevance
“…The previous results agree with those of Rozenboim et al (2004), Cao et al (2008 and Angélica Mendes et al (2013) who found that the chickens exposed to light emitted from white LED lamps had the least FC and the better FCR than did chickens reared under the other light sources. Moreover, significant differences in FC and FCR of birds exposed to light emitted from different light sources were observed by Riber (2015), Huth and Archer (2015) and Olanrewaju et al (2015). Also, Hossein and Zaghari (2016) reported that the FCR was lowest at birds reared under light emitted from warm-white light LED lamps compared to the reared under the light emitted from the incandescent lamps.…”
Section: Feed Consumption and Feed Conversion Ratiomentioning
confidence: 97%
See 2 more Smart Citations
“…The previous results agree with those of Rozenboim et al (2004), Cao et al (2008 and Angélica Mendes et al (2013) who found that the chickens exposed to light emitted from white LED lamps had the least FC and the better FCR than did chickens reared under the other light sources. Moreover, significant differences in FC and FCR of birds exposed to light emitted from different light sources were observed by Riber (2015), Huth and Archer (2015) and Olanrewaju et al (2015). Also, Hossein and Zaghari (2016) reported that the FCR was lowest at birds reared under light emitted from warm-white light LED lamps compared to the reared under the light emitted from the incandescent lamps.…”
Section: Feed Consumption and Feed Conversion Ratiomentioning
confidence: 97%
“…In addition to the green LED lamps illumination could improve the antioxidative capacity and secretion of melatonin to promote B lymphocyte proliferation of bursa of fabricius in young broilers (Li et al, 2015). Moreover, Riber (2015), Huth and Archer (2015), Hossein and Zaghari (2016) and Olanrewaju et al (2016) found that the carcass traits, giblets and immune organs improved in birds reared under light emitted from LED lamps compared to the other sources. On the other hand, Deep et al (2010), Farghly and Abdel-nabi (2011), Farghly et al (2015b, Ahmed et al (2015) and Mohamed et al (2017) who reported that most of the carcass characteristics for poultry species (broilers, Dandarawi chickens and Japanese quail) were not affected by various light sources.…”
Section: Carcass Traitsmentioning
confidence: 98%
See 1 more Smart Citation
“…Inadequate temperature [32][33][34][35][36][37][38][39] Inadequate ventilation and increased dust [1,18,19,40,41] Inadequate lightning [1,18,19,42,43]…”
Section: Technological Stressorsmentioning
confidence: 99%
“…Some interesting studies demonstrated a long time ago that supplementary light increased milk yield [28], but today, we also know that certain lighting conditions can also avoid some diseases in cows [29], which means important savings in drugs, loss of production, profit from meat and, in summary, more sustainable cow ranching. Concerning chickens, an accurate period of light exposure also impacts the circadian rhythms, with a subsequent increase in growth and positive impact without higher environmental impact [30,31].…”
Section: Non-conventional Uses Of Lightingmentioning
confidence: 99%